First Autonomous Underwater Vehicle Observations of a Potential Petrale Sole (Eopsetta jordani) Spawning Aggregation Off the US West Coast - Powell, Abigail; Clarke, M. Elizabeth; Haltuch, Melissa A.; Fruh, Erica; Anderson, Jeffrey; Whitmire, Curt E.; Johnson, Melanie M. (Frontiers in Marine Science, 2022)
Understanding the timing and reproductive behavior of commercial fish species is a key part of well-informed stock assessments and fishery management, but this information is often limited, particularly for species that spawn in deep water. Petrale sole (Eopsetta jordani) is one of the most commercially important flatfish species in the US and is known to spawn during winter. A number of spawning grounds have been identified using catch data and tagging studies, but to our knowledge there have been no direct visual observations of aggregating petrale sole. In 2018, we observed unusually high densities of petrale sole in autonomous underwater vehicle (AUV) imagery collected at a feature inshore of Santa Lucia Bank off the California coast. In addition to aggregations of fish, we observed fish in positions and configurations that we believe to be related to spawning including physical contact between individuals and evidence of consistent size differentiation within clusters. We present images of the aggregating petrale sole and information on the physical and environmental conditions at this site. We also compare these observations to the results of AUV surveys carried out in 2005 at this location. Analysis of commercial catch data from this area supports the hypothesis that this is a seasonal petrale sole aggregation as fishing at this site occurs mainly during winter months with catches dominated by petrale sole. In addition to the potential identification of a spawning aggregation, these observations show how advanced technologies can provide insight into the reproductive behavior of a commercially important species.